2020
DOI: 10.3390/agronomy10050692
|View full text |Cite
|
Sign up to set email alerts
|

Technology Adoption and Extension Strategies in Mediterranean Agriculture: The Case of Family Farms in Chile

Abstract: Extension services play a crucial role by improving skills and access to information that result in greater farm level innovations, especially on family farms which are the predominant form of agriculture in the world. This study analyzed the connection between strategies implemented by extension services and technology adoption on family farms. Using the case of the Servicio de Asesoría Técnica (SAT) Program, we developed a bottom-up adoption index (AI) for vegetable and berry farmers in three regions of Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…The production efficiency and scale of apples in different provinces are different in different years. To explore the specific influence and connection, this study uses DEAP2.1 software [33][34][35][36] to calculate the total factor production efficiency of seven provinces and cities from 2008-2018. In addition, when using the DEA method for measurement, the dynamic change in the total factor production efficiency of each province is analyzed, and the analysis method also further measures the technical progress and technical efficiency of each province.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production efficiency and scale of apples in different provinces are different in different years. To explore the specific influence and connection, this study uses DEAP2.1 software [33][34][35][36] to calculate the total factor production efficiency of seven provinces and cities from 2008-2018. In addition, when using the DEA method for measurement, the dynamic change in the total factor production efficiency of each province is analyzed, and the analysis method also further measures the technical progress and technical efficiency of each province.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, production efficiency and scale can develop on a certain scale. According to one study, seven Chinese apple-producing areas can undergo moderate-scale cultivation [34,35], namely land circulation dispersal, fragmentation of land circulation to apple operation at large, professional cooperatives, and other ways to realize centralized management. All of these can produce the scale effect and improve the efficiency of apple production.…”
Section: Plos Onementioning
confidence: 99%
“…The many services provided by extension agents are essential to motivate farmers to innovate and guide them in their implementation, especially in developing rural agriculture in underdeveloped economies due to the high rates of poverty and illiteracy there. Rojas et al (2020), Timprasert et al (2014), and Kassie et al (2013) revealed a clear positive association between access to and/or visits to extension agents and adoption of SAPs. Many studies detect that creating farmer networks, participation in training courses are influential factors in the adoption of SAPs (Kassie et al, 2013;Timprasert et al, 2014).…”
Section: Factors Influencing Saps Adoptionsmentioning
confidence: 94%
“…There have been several studies on the factors influencing technology adoption of new or improved technologies and practices in relation to grower characteristics, method of information transfer, attitudes and kind of technology (Kumar et al, 2018;Martínez-garcía et al, 2016). Adoption is often approached from a technology push perspective and is judged in terms of a scale ranging from "innovators," "early adopters," "late adopters," to "laggards (Valente, 1996); however, these farmers scales can also be associated with the potential effect of a new technology depends on whether farmers adopt it and, if they do, whether the adoption is to the extent that it can deliver results in a certain period of time (Jara-Rojas et al, 2020).…”
Section: Agricultural Technology Adoptionmentioning
confidence: 99%